Biomechanical aspects of performance enhancement and injury prevention in alpine ski racing - Spörri, J. (2012)
Competitive alpine ski racing is a spectacular and fascinating sport attracting the public interest. For many decades, substantial efforts have been undertaken to enhance the athlete`s performance by various players, such as national sport federations and equipment suppliers. As a consequence of exploring the limits of the sport, the incidence and severity of injuries have been become alarmingly high. From previous studies it is known that more than one third of the World Cup (WC) athletes are injured each season, and that up to 72 per cent have sustained at least one severe injury during their careers. Even though in recent years significant efforts have been made to reduce these injuries, preventive measures are still not as effective as they could be. This is due to the fact that the causes of injuries are still not well understood and the knowledge about the influence of potential prevention strategies on biomechanical variables related to injury risk is still poor. With respect to performance enhancement, there is a similar situation: even though alpine ski racing is a highly developed sport in terms of business, equipment, and training concepts, there is still a lack of functional and biomechanical understanding of the performance relevant factors. This lack of knowledge often leads to a situation that performance enhancement is only achieved occasionally by the principle of "trial and error". Hence, there is an evident need for a more detailed understanding of biomechanical aspects related to performance enhancement and injury prevention in alpine ski racing. Therefore, this thesis has three main purposes: (1) to assess current performance prediction/enhancement concepts used in science and/or coaching; (2) to compile and to explore perceived key injury risk factors; and (3) to assess the potential injury prevention strategy of increasing the horizontal gate distance in order to reduce speed. For these purposes a video-based 3D kinematic field measurement with a top world class athlete and explorative qualitative interviews with expert stakeholders were conducted. Regarding the first purpose, it was found that none of the existing performance prediction/enhancement concepts were able to entirely explain time differences between different performed turns of a top world class athlete. This might be explained by the fact that these concepts address only isolated aspects of ski racing performance. Hence, for both science and coaching, there is a need for more comprehensive approaches that include all variables influencing performance in one concept. Comparing the characteristics of fast and slow turns, it was found that the skier`s line and timing played a major role for time over short sections. Fast turns were initiated higher regarding the vertical position on the slope plane and were turned less out of the direction of the fall line. Concerning the second purpose, a total of 32 perceived risk factors categories were derived from the expert stakeholder interviews within the basic categories Athlete, Course, Equipment and Snow. Regarding their perceived impact on injury risk, the experts` top five categories were found to be: system ski, binding, plate and boot; changing snow conditions; speed and course setting aspects; physical aspects of the athletes; and speed in general. Finally, in relation to the third purpose, it was found that in order to considerably reduce speed by increasing the horizontal gate distances, substantial course setting changes might be needed, since racers are able to adapt and partly compensate by changing their timing strategies. Furthermore, it was found that there might be two safety drawbacks of controlling speed by increased horizontal gate distances: increased fatigue and higher risk of out-of-balance situations. In summary, this doctoral thesis has added a substantial contribution to the current body of knowledge and provided more detailed hypotheses for further studies that are based on both scientific indication and stakeholders` knowledge. However, due to the explorative character of this thesis, further studies should verify the plausibility of the findings and investigate the more detailed hypotheses